Activities of the Czechoslovak Youth Union at Palacky niversity in the end of 40th and at the beginning of the 50th of the 20th Century - Sukova, Monika; Kopecek, Pavel (Civilia, 2020)
The present study focuses on the activities of university students between 1948 and 1952 in the context of the development of the Czechoslovak Youth Union at Palacky University in Olomouc. The topic of university students in the second half of the twentieth century has been studied in detail in contemporary historical research, especially in connection with the years 1948, 1968 and 1989 as the turning points of the Czechoslovak history. However, the gap between these milestones offers the focus areas that have not been researched yet. In this paper, we focus on extracurricular activities of students of Palacky University under the patronage of the Czechoslovak Youth Union, which was closely linked to the politics and ideology of the Communist Party of Czechoslovakia. The Communists perceived the danger of uncontrolled spending of free time by university students, so they monitored their actions and eventually censored and restricted them. In the 1950 s, students were offered activities supporting mainly socialist cohesion and Marxist-Leninist perception of the world, such as part time jobs, party trainings, competitions at faculty dormitories, thematic professional lectures, etc.
Keywords: University students; Czechoslovak Youth Union; Communist regime; Palacky University in Olomouc